In hospitalized patients with communityacquired pneumonia, do corticosteroids improve outcomes?. Issue 5 (May 2018) - Seferovic, Admir; Pippin, Phillip; Larsen, David; Dianes, Gabriel; Oyler, Vincent
Abstract : EVIDENCE‐BASED ANSWER : Yes. Corticosteroids in hospitalized patients with community‐acquired pneumonia decrease the length of non‐intensive care unit hospital stays by 1 day, time to clinical stability by 1 day, need for mechanical ventilation by 55%, and progression to acute respiratory distress syndrome (ARDS) by 76%. Corticosteroids decrease mortality in cases of severe community‐acquired pneumonia (SOR: A, meta‐analyses of RCTs).